Pengaruh Kompetensi Dan Promosi Jabatan Terhadap Kinerja Karyawan Di Perusahaan Kaliau Mas Perkasa Kabupaten Sambas - admin, Merry Putri Stefina Sawit B1021161092 (Jurnal Manajemen Update, 2021)
This study aims to examine and analyze the effect of competence and job promotion on the performance of employees of PT Kaliau Mas Perkasa. This type of research is causal associative with a quantitative approach. The population in this study were employees of PT. Kaliau Mas Perkasa of the Sambas area, which already has a career path of 35 employees using the census method. The data analysis model used is multiple linear regression analysis using SPSS version 20.0. Based on the results of the study showed that competence and promotion have a significant effect on employee performance. The ability of these variables in explaining their effects on employee performance was 57.5% while the remaining 42.5% was explained by other factors outside the research model. Keywords :      competence, job promotion, employee performance DAFTAR PUSTAKA Hasibuan, Malayu S.P. (2014). Manajemen Sumber Daya Manusia, Edisi Revisi. Jakarta: Bumi Aksara.Iko Oktafiasari. (2017). Pengaruh Promosi Jabatan, Mutasi, dan Kompensasi Terhadap Kinerja Karyawan Pada Bank Jatim Cabang Kediri. Simki-Economic Vol. 01 No. 08 Tahun 2017 ISSN:BBBB-BBBB, Artikel Skripsi Universitas Nusantara PGRI Kediri.Japerdi Wijayanto, Lucky O. H. Dotulong. (2017). Pengaruh Pelatihan, Kompetensi, Motivasi terhadap Kinerja Karyawan pada PT. Plasa Multi Krindo Manado. Jurnal EMBA Vol 5.Navratin Datu Sabar, Adolfina, Lucky O.H. Dotulong. (2017). Pengaruh Promosi Jabatan dan Mutasi Kerja Terhadap Kinerja Pegawai, Vol 5 No 2. 404 – 413.Rivai, Veithzal. (2014). Manajemen Sumber Daya Manusia, Human Resources Management, Jilid 2. Jakarta: Gunung Agung.Robbins, Stephen, P. (2003). Perilaku Organisasi. Jilid 1. Edisi 9. Penerjemah Tim Indeks. Jakarta: PT. Indeks, Gramedia Grup.Sutrisno, Edy. (2012). Manajemen Sumber Daya Manusia. Jakarta: Kencana.Winda Yulyarta Simanjuntak. (2015). Pengaruh Promosi Jabatan Terhadap Kinerja Karyawan Pada PT. Riau Media Grafika/Tribun Pekanbaru. Volume 2 No 2.Yannik Ariyanti, Andri Veni. (2019). Pengaruh Kompetensi Pelatihan Dan Promosi Jabatan Terhadap Kinerja BPR Majesty Golden Raya Batam. Vol 6 No.1.